2015
DOI: 10.1186/s13104-015-1226-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pain among a group of Nigerian dental patients

Abstract: BackgroundPain is considered a key symptom associated with possible impairment of oral-health-related quality of life and its assessment is important for the planning and evaluation of preventive and treatment effort. The tools for assessing pain must therefore be valid and consistent. The objective of this study was to assess dental patients’ level of pain based on the clinical diagnosis of their dental condition and the correlation between two pain assessment scales, Visual analogue scale (VAS) and the Full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 26 publications
(24 reference statements)
3
22
0
Order By: Relevance
“…Several previous articles suggested the use of unidimensional scales to measure acute pain [ 5 6 20 21 22 23 24 25 ], caused by trauma, surgery, childbirth, or an acute medical disease. Previous OMFS articles mostly used the VAS for pain assessment in acute pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous articles suggested the use of unidimensional scales to measure acute pain [ 5 6 20 21 22 23 24 25 ], caused by trauma, surgery, childbirth, or an acute medical disease. Previous OMFS articles mostly used the VAS for pain assessment in acute pain.…”
Section: Discussionmentioning
confidence: 99%
“…Polly et al [ 27 ] suggested that the verbally administered the NRS can be related to the VAS in acute pain measurement. Unfortunately, the VAS has also been mentioned to have more practical difficulties than the VRS and the NRS [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic dental pain prevalence was reported as 25-27% in Nigeria. In this study, the Visual Analog Scale and the Full Cup Test were of similar sensitivity for pain assessments [48]. Indian children in East Delhi assessed their post dental extraction pain as 0.73-4.38/10 using both a visual analog scale and faces pain scale, with decreasing pain with older age.…”
Section: Reviewmentioning
confidence: 99%
“…Chronic dental pain prevalence was reported as 25–27% in Nigeria. In this study, the Visual Analog Scale and the Full Cup Test were of similar sensitivity for pain assessments [ 46 ]. Indian children in East Delhi assessed their post dental extraction pain as 0.73–4.38/10 using both a visual analog scale and faces pain scale, with decreasing pain with older age.…”
Section: Reviewmentioning
confidence: 99%